(untitled) (Proceedings of International Conference on Special Education, 2015)
Since the regulation of Inclusive Education for Children with Special Needs and with Talent and Giftedness was endorsed in 2009, public schools in Indonesia have incorporated various forms of inclusive practices recognising the context of each school. Following this, school level reviews have focused on readiness and effectiveness of schools in delivering inclusive practices. Nevertheless, little attention has been given to the voice of children and their perspectives on current inclusive practices in the Indonesian context. This paper aims to understand current inclusive practices in one Indonesian primary school through the lens of their students. A phenomenological inquiry was employed to examine children’s experience about the principles of inclusion and inclusive practice at their schools. We listened to individual children and groups of children, with and without special needs, as they talked about inclusion, exploring what inclusion may mean for them, and how they feel about it. Through the use of student drawings and school photo diaries, the study examined how children viewed the enactment of inclusive practices. In this particular case study, we reflect on the affordances of visual methods leading to narratives of experiences and voices of the students in special and regular classrooms within an inclusive primary school. Unique experiences of ‘inclusion day’, students being moved from special classrooms to mainstream classrooms and vice versa, students with special needs spending part of their day in the regular classrooms characterize the stories. Themes identified from students’ accounts such as friendship, meaning of being ‘regular’ and ‘special’, and participation will be explored. These themes will be contrasted with themes that have emerged from parents and teacher groups, including leadership, personal values, change, and value of academic achievement. Finally, we will discuss the experiences of the students as researchers investigating their own questions of inclusion.